Poststroke cognitive impairment among stroke survivors in Sub-Saharan Africa: a systematic review and meta-analysis - Tigabu Munye Aytenew; Demewoz Kefale; Binyam Minuye Birhane; Solomon Demis Kebede; Worku Necho Asferie; Amare Kassaw; Yenework Mulu Tiruneh; Getasew Legas; Addisu Getie; Berihun Bantie; Sintayehu Asnakew (BMC Public Health, 2024)
Abstract Introduction Stroke is the leading cause of death and disability among adults and elderly individuals worldwide. Although several primary studies have been conducted to determine the prevalence of poststroke cognitive impairment among stroke survivors in sub-Saharan Africa, these studies have presented inconsistent findings. Therefore, this study aimed to determine the pooled prevalence of poststroke cognitive impairment and identify its associated factors among stroke survivors in sub-Saharan Africa. Methods The studies were retrieved from the Google Scholar, Scopus, PubMed, and Web of Science databases. A manual search of the reference lists of the included studies was performed. A random-effects DerSimonian-Laird model was used to compute the pooled prevalence of poststroke cognitive impairment among stroke survivors in sub-Saharan Africa. Results A total of 10 primary studies with a sample size of 1,709 stroke survivors were included in the final meta-analysis. The pooled prevalence of PSCI was obtained from the 9 included studies with a sample size of 1,566. In contrast, the data regarding the associated factors were obtained from all the 10 included studies with a sample size of 1,709. The pooled prevalence of poststroke cognitive impairment among stroke survivors was 59.61% (95% CI: 46.87, 72.35); I2 = 96.47%; P < 0.001). Increased age (≥ 45 years) [AOR = 1.23, 95% CI: 1.09, 1.40], lower educational level [AOR = 4.35, 95% CI: 2.87, 6.61], poor functional recovery [AOR = 1.75, 95% CI: 1.42, 2.15], and left hemisphere stroke [AOR = 4.88, 95% CI: 2.98, 7.99] were significantly associated with poststroke cognitive impairment. Conclusions The pooled prevalence of poststroke cognitive impairment was considerably high among stroke survivors in sub-Saharan Africa. Increased age, lower educational level, poor functional recovery, and left hemisphere stroke were the pooled independent predictors of poststroke cognitive impairment in sub-Saharan Africa. Stakeholders should focus on empowering education and lifestyle modifications, keeping their minds engaged, staying connected with social activities and introducing rehabilitative services for stroke survivors with these identified factors to reduce the risk of developing poststroke cognitive impairment.